Assessment of the effectiveness of non-pharmacological methods in pain relief during labor - Samara Maria Borges Osório; Lourival Gomes da Silva Júnior; Ana Izabel Oliveira Nicolau (Rev Rene)
This is a systematic review that aimed to evaluate the effectiveness of non-pharmacological methods for pain relief during labor. The articles’ selection was based on BDENF, PubMed, LILACS and Cochrane Library, published between 2007 and 2012. One analyzed seven studies that assessed the non-pharmacological methods and met the eligibility criteria. It was evident that massage, aromatherapy, immersion bath, acupuncture and acupressure are effective methods to relieve pain during labor, because besides reducing pain perception, they still lower levels of anxiety and stress. Among them, the most efficient one was the massage, mainly when done in the first stage of labor. Furthermore, the interventions don’t interfere in the kind and duration of labor, being safe to clinical practice.